Overexpression of Arabidopsis molybdenum cofactor sulfurase gene confers drought tolerance in maize (Zea mays L.). - Yao Lu; Yajun Li; Jiachang Zhang; Yitao Xiao; Yuesen Yue; Liusheng Duan; Mingcai Zhang; Zhaohu Li (PLoS ONE, 2013)
Abscisic acid (ABA) is a key component of the signaling system that integrates plant adaptive responses to abiotic stress. Overexpression of Arabidopsis molybdenum cofactor sulfurase gene (LOS5) in maize markedly enhanced the expression of ZmAO and aldehyde oxidase (AO) activity, leading to ABA accumulation and increased drought tolerance. Transgenic maize (Zea mays L.) exhibited the expected reductions in stomatal aperture, which led to decreased water loss and maintenance of higher relative water content (RWC) and leaf water potential. Also, transgenic maize subjected to drought treatment exhibited lower leaf wilting, electrolyte leakage, malondialdehyde (MDA) and H(2)O(2) content, and higher activities of antioxidative enzymes and proline content compared to wild-type (WT) maize. Moreover, overexpression of LOS5 enhanced the expression of stress-regulated genes such as Rad 17, NCED1, CAT1, and ZmP5CS1 under drought stress conditions, and increased root system development and biomass yield after re-watering. The increased drought tolerance in transgenic plants was associated with ABA accumulation via activated AO and expression of stress-related gene via ABA induction, which sequentially induced a set of favorable stress-related physiological and biochemical responses.